Looking Back : Raton's Bee Ferrero poses (Raton, New Mexico Raton Range, 1978)
Raton's Bee Ferrero poses for her first solo flight in 1935. She was the state's first female aviatrix. Mrs. Ferrero loaned this photgraph to the Range's "Looking Back" series.
Mater List Item # 4
File location is in the New Mexico File Cabinets
Keywords: Ferrero, Bee; Pilot; First Female Airpilot; Raton, New Mexico